INDONESIAN GRADUATE STUDENTS’ CHALLENGES IN UNDERSTANDING ENGLISH JOURNAL ARTICLES - Nariza Ayu Pasha; Shifak Aisyah; Retno Vinsi Damayanti; Surono Surono (PROJECT (Professional Journal of English Education), 2024)
For academic purposes, higher education students need to analyze the information in English journal articles to write academic articles and graduate students are no exception. Furthermore, this study was conducted to investigate and explore the challenges in comprehending English journal articles faced by graduate students, and their strategies to overcome the difficulties. The respondents of the study were first and second-semesters of graduate students of English Education graduate students in two private universities in Surakarta and Yogyakarta, Indonesia. The qualitative research design used open-ended questionnaires and forum group discussions to collect the data. The results of this study indicated that the difficulties students face when understanding journal articles were lack of vocabulary, unfamiliar academic vocabulary, boredom with reading long texts, difficulties in finding the details, and unfamiliar sentence structure and different culture with the author. To overcome this problem, there were five categories of ways for students: getting used to reading, creating a comfortable atmosphere when reading, using a dictionary to translate the text, enriching new vocabulary, looking for simpler articles, and using appropriate reading strategies. Therefore, this research can provide reflection and evaluation of lecturers and students in the teaching and learning process in enhancing students’ reading skills.